Ultrasonic investigations of the relaxation processes related to the presence of the group –C = 0/NH in molecules - BARTYNOWSKA-MEUS, Zofia; JUSZKIEWICZ, Adam (Archives of Acoustics, 1983)
Measurements of the velocity and the absorption coefficient of ultrasound were taken in monosubstituted amides as a function of temperature and frequency. It was found that a single relaxation process related to rotation of molecules around the C–N bond occurs over the temperature and frequency range investigated. Termodynamic parameters which characterize the process observed were determined.